Never too late for love - Ayodele, S.O (Evans Brothers [Nigeria Publishers] Limited, 2006)
Professor Adelu, popularly called 'Prof. Divorce' on account of his failed marriage and his unwavering disdain to the institution of marriage,suddenly encounters love in a most unlikely manner when he meets Patricia, a junior lecturer in his department. His resolution not to re-marry fades away into oblivion and within a short while, preparations begin for their wedding. However, a week to the solemnization, the worst happen...Will the love birds survive the tumult?
Keywords: Fiction; Juvenile Literature